A new constitutive equation on ice materials - Ince, Serdar Turgut; Kumar, Ankush; Paik, Jeom Kee (TAYLOR & FRANCIS LTD, 2017)
The structural crashworthiness analysis involving buckling, plasticity, crushing, and fracture with the strain-rate effects is required to evaluate the characteristics of structural deformations and impact energy dissipation at the event of collisions between ships or offshore platforms and icebergs. The constitutive equations of both steels and ice materials should be characterised for numerical computations as the collision impact energy is dissipated by the two colliding and deformable bodies, namely not only ships or offshore platforms but also icebergs. The primary objective of the present study is to examine ice properties and propose a constitutive equation of ice materials which shall be implemented into nonlinear finite element method computations of the structural crashworthiness associated with the collisions. Previous studies are first surveyed in terms of the influencing parameters as the many uncertainties involved make the problem highly complex. The parameters affecting the mechanical properties of ice materials are then discussed. In addition to referencing the existing test database associated with the mechanical properties of ice materials, a new test database is obtained by laboratory testing of the authors' group. Based on findings from the existing and the new test database, a new constitutive equation used for ice materials is proposed associated with quasi-static and impact responses.
Keywords: constitutive equation on ice materials; Johnson-Cook constitutive equation; ice material, structural crashworthiness; impact; MECHANICAL-PROPERTIES; COMPRESSIVE STRENGTH; STRAIN; FRACTURE; ICEBERG; FAILURE; PLASTICITY; PARAMETERS; 1ST-YEAR; VELOCITY; Engineering